Tinjauan Literatur Tentang Pengaruh Penggunaan Alat Pelindung Diri (APD) Terhadap Tingkat Kecelakaan Kerja - Annisa Zahria Putri Handayani; Andriyani Andriyani; Triana Srisantyorini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Workplace accidents are a crucial issue that greatly impact worker safety and business continuity. This study aims to evaluate the influence of Personal Protective Aquipment (PPE) usage on reducing workplace accident rates across various sectors, including construction, healthcare, and manufacturing. Using a qualitative descriptive approach through a literature review of fifteen scientific articles published between 2020 and 2024, obtained from databases such as Google Scholar, this research found that PPE usage significantly contributes to reducing the incidance of workplace accidents. Compliance with PPE usage is influenced by workers knowledge, attitudes, length of service, and education level, supported by company supervision and the comfort of PPE use. The findings also indicate that the provision of PPE must be accompanied by education, training, and strict supervision to achieve optimal effectiveness. This study emphasizes the importance of implementing a comprehensive accuptional safety management system to build a strong and sustainable safety culture in the workplace.